step 1; a=b
step 2; a^2=ab (multiplying both sides by a)
step 3; a^2-b^2=ab-b^2 (subtracting both sides by b^2)
step 4; (a+b)*(a-b)=b(a-b)
step 5; (a+b)=b (cancelling (a-b) from both sides)
step 6; 2*b=b (as a=b from step 1)
therefore, 2=1 (cancelling b from both the side)

## Comments

Sort by:

TopNewestthnx for answering – Haque Farazul · 4 years, 3 months ago

Log in to reply

step 5 is wrong due to dividing by 0 – Bhuvnesh Goyal · 4 years, 3 months ago

Log in to reply

step 5 is wrong because you are cancelling (a-b) from both sides which according to step 1 is equal to zero. Dividing by zero is incorrect. – Surya Prakash · 4 years, 3 months ago

Log in to reply

– Raja Metronetizen · 4 years, 3 months ago

yes the step 5 is incorrect and the procedure includes diving by 0 i.e.(a-b) is absolutely wrong...leading to wrong result...:)Log in to reply